From Polydeoxyribonucleotides (PDRNs) to Polynucleotides (PNs): Bridging the Gap Between Scientific Definitions, Molecular Insights, and Clinical Applications of Multifunctional Biomolecules - Cíntia Marques; Alexandre Porcello; Marco Cerrano; Farid Hadjab; Michèle Chemali; Kelly Lourenço; Basste Hadjab; Wassim Raffoul; Lee Ann Applegate; Alexis E. Laurent (Biomolecules)
Polydeoxyribonucleotides (PDRNs) and polynucleotides (PNs) are similar DNA-derived biopolymers that have garnered significant scientific attention since the 1990s for their potential applications in wound healing and skin rejuvenation. These biopolymers exhibit a broad molecular weight (MW) range, typically spanning from 50 to 1500 kDa. However, recent studies have expanded this range to encompass fragments as small as 1 kDa and as large as 10,000 kDa. Clinically, PDRN/PN formulations, commercially available in various galenic forms (gels, creams, serums, masks, and injectables), have demonstrated promising effects in significantly promoting skin regeneration, reducing inflammation, improving skin texture, preventing scar formation, and mitigating wrinkles. Importantly, despite their widespread use in cosmetology and aesthetic dermatology, the interchangeable use of the terms “PDRN” and “PN” in the scientific literature (to describe polymers of varying lengths) has led to considerable confusion within the medical and scientific communities. To specifically address this PDRN/PN ambiguity, this narrative review proposes a standardized structure-based nomenclature for these DNA-derived polymers, the “Marques Polynucleotide Cutoff”, set at 1500 kDa. Thus, we propose that the term “PDRN” should be exclusively reserved for small- and medium-chain polymers (MW < 1500 kDa), while the term “PN” should specifically be used to denote longer-chain polymers (MW ≥ 1500 kDa). In a broader perspective, this classification is based on the distinct physicochemical properties and therapeutic effects of these DNA fragments of various MWs, which are comprehensively discussed in the present review.